Prospects and perspectives of virtual in-vitro toxicity studies on herbal extracts of Terminalia arjuna with enhanced stratagem in Artemia salina model: a panacea to explicit the credence of solvent system in brine shrimp lethality bioassay - Meena, D. K.; Sahoo, A. K.; Swain, H. S.; Borah, S.; Srivastava, P.P.; Sahu, N.P.; Das, B. K. (Emirates Journal of Food and Agriculture, 2020)
An in-vitro toxicity study was undertaken for the validation, laydown the standards, supplement some of the information on assessment and define the nature of toxicity of different solvent extracts of Terminalia arjuna considering Artemia salina model, as a case study. In the present study, experimental conditions such as yellow color light of 100 W at 5% salinity for 48 hours with pH 8.0-8.5 at 30 0C, picking up of nauplii with 3mL dropper cut at its tip, 24 hours incubation in same experimental conditions and visualization with 50X magnifying glass were modified unlike previous studies. Functional screening of solvent extracts with their mother solvents revealed that hex, Etac, Chlo, Acet, Etoh, and Meoh exhibited, the LC50 values as 118.50, 101.75, 93.36, 278.32, 528.78 and 477.67 ppm, respectively, designating them as; medium, medium, high, medium, low, medium toxic, while in their solvent extract forms the toxicity nature gets changed indicating the effectiveness of the extracts. Study, also defines the toxicity level for universal solvents such as DMSO and Dw as to be non-toxic as per the Meyers toxicity index and Clarkson’s toxicity criterion. Among solvent extracts of T. arjuna, all were found to be toxic as per Meyers toxicity index. However, with reference to Clarkson’s toxicity criterion, solvent extracts comprehended extended toxicity classes as low, medium and high toxic. The PCA 1 and 2 showed, 69.46% and 19.74% variations indicating strong correlation between the parameters. The results confirmed that LC50 of any solvent extract could be treated as relative LC50, which is the fraction of mother solvent and could be treated as absolute LC50, which is the actual potential of the solvent extracts that might be positive for less effective and negative for highly effective solvent extracts. For smoothening of experimental results, negative sign was ignored. Relative LC50, relative LC50%, absolute LC50, and absolute LC50% could find liner relation with their % fractions and inverse relation with their counterparts. Thus present study advocates the inclusion of relative LC50, relative LC50%, , absolute LC50, absolute LC50%, considerating 95% upper and lower fiducial class intervals and TI values while fixing the nature of toxicity and designating the safety aspect to the host. Also, the study recommends for the collective effort to make BSLA as an internationally accepted and robust standard by revisiting and supplementing the existing toxicity criterion for the BSLA.